The Role of Teacher Discipline in Improving Elementary School Student Learning Outcomes - Supit, Deisye; Baureh, Gabriella Alleid Dian; Rakmeni , Ade Putri (12th International Scholars Conference 2025, 2026)
This study aimed to analyze the relationship between teacher discipline and the learning outcomes of Grade V students at SD Advent Unklab. Using a quantitative correlational design, data were collected from 58 students through questionnaires and mid-semester mathematics scores. Descriptive analysis revealed that the level of teacher discipline was in the high category and student learning outcomes were in the good category. However, Pearson correlation analysis showed no significant relationship between teacher discipline and student learning outcomes. These findings suggest that, despite the high level of teacher discipline, it does not significantly influence students' mathematics learning outcomes in this context. The study highlights the need for schools and teachers to continuously maintain and improve discipline while also considering other factors that may impact learning outcomes.